Nutritional Quality of Undergraduate Student Meals in an All-You-Care-to-Eat Campus Dining Facility (P04-156-19). (13th June 2019) - Olson, Audrey; Vieyra, Katie; Polasky, Alexandra; Best, Amy; Durant, Lois; Frankenfeld, Cara; Slavin, Margaret
Abstract: Objectives: To assess the overall nutritional quality of meals chosen by undergraduate students during weekday lunches at campus all-you-care-to-eat dining halls. Methods: A previously validated exit survey was used to collect self-reported data from undergraduate students on foods and beverages they consumed during a single visit to two all-you-care-to-eat dining halls on the George Mason University Fairfax campus, during 4 weeks. ( n  = 468) Nutritional quality of each meal was evaluated on a 7-point rubric, according to the 'Wellness Meal' standards from the Partnership for a Healthier America: ≤700 kilocalories,  ≤10% calories from saturated fat,  ≤800 mg sodium,  ≥2 ounces whole grains,  ≥1 cup lowfat dairy,  ≥ 1.75 cups fruits and vegetables, and ≥ 2 ounces lean protein. Results: Of the maximum score of 7 on the meal nutritional quality rubric, 4 participants earned the highest score of 5, whereas 43, 150, 132, 88, and 51 participants had scores of 4, 3, 2, 1, and 0, respectively. The most commonly attained rubric standard was saturated fat, where 60% of participants consumed ≤ 10% calories from saturated fat and average consumption was 9.1% (± 5.4%) of calories. The least achieved rubric category was lowfat dairy, where only 2% of students consumed 1 cup equivalent, followed by only 9% of participants having consumed the 2 ounce equivalent of whole grains. Approximately one-third of students met calorie, lean protein, sodium, and fruit/vegetable standards. Conclusions: Despite a wide variety of food options in the campus all-you-care-to-eat dining halls during the lunch hours, most undergraduate students consumed meals of subpar nutritional quality, with the vast majority meeting fewer than half the categories on the meal nutritional quality rubric. All-you-care-to-eat university dining halls may be a prime location for nutrition education and interventions. Funding Sources: This research was funded by the George Mason University Provost's Multidisciplinary Research Award.